Stakeholder Synergy in Realizing Muhammadiyah Vocational High School as a Center of Excellence Based on Muhammadiyah Values - Khasanah, Uswatun; Trisnawati, Septian Nur Ika; Falaah , Muhammad Fajrul (Program Pascasarjana, Universitas Islam Bunga Bangsa Cirebon, 2025)
The purpose of this study is to explore how the collaboration of stakeholders can realize SMK Muhammadiyah as a Center of Excellence based on Muhammadiyah values. The study subjects included principals, teachers, education personnel, students, parents, and business and industry (DUDI) partners, who were selected through purposive sampling techniques. Using a qualitative descriptive approach with a case study method, data were collected through in-depth interviews, observations, and document analysis. Data analysis used the Miles and Huberman model. Triangulation was applied to ensure data credibility. The findings show that effective stakeholder synergy plays an important role in optimizing curriculum relevance, improving teaching quality, and enhancing students' employability. Strong industry partnerships contribute to the development of students' practical skills through internships and work-based learning. In addition, Muhammadiyah values, such as hard work (al-jihad fi sabilillah), independence (al-istiqlal), and social concern (at-ta'awun), are integrated into the curriculum, fostering character development in addition to technical competence. This study provides an important contribution theoretically by showing that vocational education is not only oriented to the development of technical skills but also to the formation of Islamic character. Practically, the results of this study can be a model for strengthening partnerships between schools and industries through project-based learning and value integration. This study highlights the importance of involving various stakeholders in vocational education reform, providing insights for policymakers, educators, and industry leaders to advance vocational education strategies that are in line with industry demands and character-based education.